1999
DOI: 10.1002/crq.3890170205
|View full text |Cite
|
Sign up to set email alerts
|

To mediate or not to mediate: Financial outcomes in mediated versus adversarial divorces

Abstract: A statewide sample of 199 mediated and 201 adversarial divorce cases in Connecticut was analyzed for differences in financial outcomes between the two formats. No differences were found between mediated and adversarial cases in family income or liability outcomes for women, in likelihood of periodic alimony being received, or in amount of alimony received. However, women in mediated cases obtained a significantly greater percentage of assets than women in adversarial cases, periodic alimony for a significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Other studies such as Jones and Bodtker (1999) and Meyer (1992) used archival court record data to identify mediation and litigation participants and mailed self-report questionnaires to them. As for Marcus, Marcus, Stilwell, and Doherty (1999), who were interested in comparing mediation and litigation groups just…”
Section: Characteristics Of Individual Studies As Seen Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies such as Jones and Bodtker (1999) and Meyer (1992) used archival court record data to identify mediation and litigation participants and mailed self-report questionnaires to them. As for Marcus, Marcus, Stilwell, and Doherty (1999), who were interested in comparing mediation and litigation groups just…”
Section: Characteristics Of Individual Studies As Seen Inmentioning
confidence: 99%
“…As indicated in Table 1, studies either included all divorce issues in mediation or limited mediation to only childrelated issues such as custody. Specifically, Kelly (1989) and Marcus, Marcus, Stilwell, and Doherty (1999) used all-inclusive mediation while Emery, Matthews, and Wyer (1991); Jones and Bodtker (1999); and Meyer (1992) limited mediation to child-related issues.…”
Section: Characteristics Of Individual Studies As Seen Inmentioning
confidence: 99%
“…Nevertheless, Kelly () found that about 15–20 percent of mediation clients were consistently dissatisfied with aspects of the mediation process, which might be due to the mediator's competence or the expectations of disputants. Other studies also indicated some negative outcomes in mediation, including less favorable financial settlement outcomes for women, limited compliance with the agreement, limited changes in the spousal relationship, and failure to reach full agreement in the case of violent couples (Marcus, Marcus, Stilwell, & Doherty, ; Mathis & Tanner, ; Pearson & Thoennes, ). Such discrepancies in client satisfaction found in these studies imply that there are a number of factors that are critical for mediation outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…These studies make significant contributions to our understanding of mediation and indicate that it is worth further investigating the effect of mediator‐related factors, such as the mediator's professional competence and mediation process, on service outcomes in different cultural and social contexts. Moreover, many empirical studies have explored outcome effectiveness in child‐related matters such as child custody, visitation arrangements, and financial support for children (e.g., Butts, ), but very few have investigated the contributing factors in finance and property disputes such as those involving alimony and property division (Marcus et al, ). Therefore, it is important to understand the contributing factors in each type of dispute and their differences, if any, to further advance our mediation knowledge and practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation